Keeping institutional logics in arm's length: emerging of rogue practices in a gray zone of everyday work life in healthcare. Issue 2 (1st July 2021) - Gürses, Serdal; Danışman, Ali
Abstract: We set out to explore the practice-level cognitive structures and associated practices characterizing the daily routine work of physicians by conducting a qualitative study in the Turkish healthcare field, in which a recent government-led healthcare reform was implemented causing logic multiplicity. Contrary to the accumulated knowledge in institutional logics literature, a bulk of which suggests that actors craft and enact various practices in managing plural and at times conflicting institutional templates strictly within the confines of higher order societal logics, this study shows that while ground level actors may not exercise complete freedom and maneuverability in relation to pre-established social structures, they do incorporate unconventional schemas of action; namely rogue practices, into their embodied practical activity, which over time become routinized in their day-to-day work lives. Unraveling the dynamics of micro-level practices of highly professionalized ground level actors as they pertain to atypical logical orientations substantially advances our understanding of the unknown or unseen side of how and under which conditions certain or various combinations of institutional logics are employed during day-to-day activities.